Komunikasi Efektif dalam Moderasi Beragama Melalui Film Dokumenter “Selaras” - Marini, Marini Marini; Salas, Hugo Julio; Kadri, Wahab Nur (Ath Thariq Jurnal Dakwah dan Komunikasi, 2023)
Religious moderation exists as an adhesive for similarities, not for sharpening differences. Many religious conflicts occur, such as rejection of the construction of places of worship, rejection of certain religious communities, hatred, hatred, hatred of places of worship, lack of peace in worship and many others. Therefore, effective communication facilities are needed to educate the public about the importance of implementing tolerance between religious communities so that life becomes harmonious. Diverse moderation is needed to be able to create peace in diversity. Therefore, the application of religious moderation in Indonesia is very necessary as a cultural strategy. There are many media that can be used, one of which is documentary films. This is also reflected in the documentary film “Selaras” which carries the theme of moderating the various people of Pekon Ambarawa Pringsewu. This research uses a qualitative approach with descriptive methods. The paradigm in this research is constructivism. The theory used in this study is the Tubbs and Moss model of effective communication theory. The results of this study it can be concluded that in the documentary "Selaras" there are various indicators of moderation.